BRAND SWITCHING MODEL AGAINST CONSUMER DISSATISFACTION ON THE SHOPEE MARKETPLACE TO OTHER MARKETPLACES - Citra Savitri; Mumun Maemunah (Politeknik APP Jakarta, 2021)
The study determines consumer dissatisfaction, variety seeking, and brand switching at Shopee's market offices. This study was conducted to determine the direct and indirect effects of consumer dissatisfaction and variety-seeking on brand switching on the Shopee marketplace to other marketplaces. The method used is quantitative with a population of Shopee users in Karawang who have switched to other marketplaces. A total of 150 samples were taken using a non-probability method of incidental sampling technique. In this paper, Consumer dissatisfaction has a positive and meaningful impact on variety seeking, variety seeking has a positive and significant effect on brand switching, consumer dissatisfaction has no significant and positive effect on brand switching, and consumer dissatisfaction has a significant and significant effect on brand switching through variety seeking.